Potensi Ekstrak Daun Nangka sebagai Biolarvasida Nyamuk Culex sp - Asro Abdi Firdaus; Setiawan .; Ferry Kriswandana (GEMA LINGKUNGAN KESEHATAN, 2018)
ABSTRACTMosquitoes are type of insect that acts as a disease vector. One of them is Culex sp mosquitos which their existence is many around us. In Indonesia there are still a lot of disease cases that caused by Culex sp mosquitos, one of them is filariasis disease. The efforts to control thecurrent population of Culex sp mosquitoes mostly use chemical insecticides. The control becomes difficult because of the resistance to chemical insecticides and adversely affects the environment. This study aims to determine the potential of jackfruit leaf extract as biolarvasida against Culex sp. The type of this study was post test onlycontrolled group design, using 625 larvae Culex sp instar III, divided into 5 groups (negative control group, 0.25% extract, 0.50% extract, 0.75% extract, extract and 1% extract). Observation was performed 24 hoursafter the treatment and counted the number of larvae death.The data were analyzed by Kruskal Wallis test followed by Post Hoc Mann-Whitney U test to determine the killing power of leafy leaf extractusing Probit analysis. The results of data analysis in this study were thedeath rate percentage of larvae after 24 hours treatment was 0% incontrol, 44% in 0.25%extract, 52% in0.50% extract, 60% in 0.75%extract,while in the extract group of 1%, the number of larval deaths was 72%. Itobtained results with significant differencein some treatment groups thatwere concentrations of 0.25% - 1%. Probit analysis showed that LC50 wasat 0.382% concentration.From results of the studyit can be concluded that jackfruit leaf extract(Artocarpus heterophyllus Lamk) was potential as Culex sp mosquitobiolarvacide. So it is necessary to conduct further research on the effectsof compounds that contained in other plant parts such as flowers, stemsand roots which will be expected to have a function asbiolarvasida.Keywords: Leaf Jackfruit, Biolarvasida, Mosquito Culex sp